The Trouble with Revisionism: or Communist History with the History Left In - Morgan, Kevin (Labour / Le Travail, 2009)
The article focuses on issues concerning revisionism, which is described by John Manley as an international historiographical tendency. It explains that one problem about the concept of revisionism was the uncertainty of method, argument and genre. It discusses the arguments of Manley about the differences of the communist parties in Canada, Great Britain and the U.S. as well as the possibility to make and break government policy in one particular country in the interests of Socialism. It also examines the impact of failing to adopt evaluative criteria on Comintern historiography.
Keywords: COMMUNIST parties; Canada; GREAT Britain; Government policy; HISTORICAL revisionism; MANLEY, John; Political Science; Socialism; United States